Finite Element Method to Study Elasto-Thermodiffusive Response inside a Hollow Cylinder with Three-Phase-Lag Effect - Bhattacharya, Debarghya; Pal, Prashanta; Kanoria, Mridula (International Journal of Computer Sciences and Engineering, 2019)
In this article, we deal with a problem of generalized elasto-thermo-diffusion interaction inside an isotropic hollow cylinder in the context of three-phase-lag model. Initially the medium is in rest and undisturbed so that all the state functions are assumed to be zero. Employing Laplace transform as a tool, the governing equations have been expressed in transformed domain, which are then solved by Galerkin finite element technique. The inversion of the transformed solution is carried out by applying a method of Bellman et al. The stresses, temperature, displacement, concentration and chemical potential are computed numerically and presented graphically in a number of figures for copper material. A comparative study for different theories (three-phase-lag model, Green-Naghdi model with energy dissipation and Lord-Shulman model) are presented. The results corresponding to thermoelastic medium (in absence of diffusion) are also carried out in a particular case. The significant points are highlighted.